ANALISIS DAMPAK IMPLEMENTASI SUSTAINABLE BUSINESS OLEH USAHA MIKRO PESERTA PROGRAM PELATIHAN DAN PENDAMPINGAN UMKM ‘Transformasi Menuju Bisnis Lestari’ - Siswanto, Fransiska Rosellya (Seminar Nasional Ilmu Terapan, 2024)
The majority of micro businesses in Indonesia are still oriented only towards profit and pay little attention to the sustainability of environmental and social aspects. This happened at the same time as the emergence of a sustainable business trend with a Triple Bottom Line approach in the worldwide. From the identification of this problem, this research was carried out to look specifically at the impact of implementing sustainable business and the importance of implementing it today. This research uses qualitative research methods. The sources for this research are five micro business actors who are participants in the MSME Training and Mentoring Program 'Transformation Towards Sustainable Business 2022’, which operates in the food and beverage sector. The data obtained is then processed through the stages of data collection, reduction and presentation, as well as drawing conclusions. As a result, it was found that the implementation of sustainable business had a positive impact on the sustainability of environmental, social and economic aspects, and fulfilled most of the targets of SDG 8 and SDG 12. There were findings that the five informants had varying levels of awareness of sustainable business, but were able to encourage informants to deepen understanding and implement the concept of sustainable business. As many as 2 out of 5 informants felt it was easy to gain access to funding. However, most informants still have problems with packaging technology that is more environmentally friendly. From this description, it can be concluded that sustainable business is essential to be implemented today.